Islamic Faith as an Ethnic Identity Marker: Overview of Sri Lanka Muslim Identity Formation, Politicization, and Violence - Imtiyaz, A. R. M. (Journal of Asian and African studies, 2025)
Since the late-19th century, for political expediency, the Sri Lankan Muslims have used Islam as a marker of identity difference which has suffered due to the tensions of religious and ethnic identity markers. Unlike Tamils and Sinhalese ethnic groups, Sri Lanka Muslim elites did not choose language as their primary identity marker but sought to differentiate themselves based on the practices and traditions of Islamic faith. These tensions have manifested in several ways, however, following the 2019 Easter Sunday attacks, there has been a great strain placed on Muslim representation as questions have been asked as to whether the religious identity has laid the foundations for the radicalization of the Muslims, especially in the wake of global Islamophobia and concerns about security. Therefore, it is important to answer questions related to Islamic identity manifestation in Sri Lanka: What is the role of an Islamic religious identity in radicalizing Sri Lankan Muslims? Why did Sri Lanka become a convenient place for IS’ activities? Did religious identity alone cause the radicalization of some Muslims? This article would attempt to answer these questions by (1) revisiting the Muslim community’s identity formation before the independence, (2) explaining Islamic identity in the post-independence Sri Lanka and the political representation to win votes and mobilize support during the ethnic civil war between Tamils and Sinhalese, and (3) analyzing factors that contributed to the radicalization of Muslims, and Islam. Drawing mostly on secondary sources, the article attempts to situate Sri Lanka Muslims’ identity formation in Sri Lanka’s ethnic conflict and reconciliation. Using answers from interviews conducted through Zoom, WeChat, and WhatsApp, the article assesses the behavior of Sri Lanka Muslims in the face of the 2019 terrorist attack by some Muslims. The article finds that religious identity alone is not sufficient to trigger violence, as evidence suggests that underlying socio-economic as well as political grievances produce polarization and radical actions. We argue that long-standing arguments tying radical actions solely to religion may require substantial revision and need to be situated within a wider frame of national reconciliation especially if it does not consider existing contexts.